2001
DOI: 10.1001/archpedi.155.7.765
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Paternal Recreational Drug Use and Sudden Infant Death Syndrome

Abstract: There was no association between maternal recreational drug use and SIDS. Paternal marijuana use during the periods of conception and pregnancy and postnatally were significantly associated with SIDS. The role of paternal psychoactive drug use, especially the relationship between marijuana and SIDS, is an understudied area; however, before any definitive role for the father can be confirmed, these findings should be investigated and replicated in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 24 publications
(42 reference statements)
0
23
0
1
Order By: Relevance
“…Dose may also be important. A case-control study of 239 infants who died of SIDS found no association between maternal recreational drug use and SIDS [177]. Of note, among opioid-exposed neonates, the risk of SIDS has been shown to relate to the severity of drug withdrawal, which correlates with the degree of maternal drug use in many studies [176].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Dose may also be important. A case-control study of 239 infants who died of SIDS found no association between maternal recreational drug use and SIDS [177]. Of note, among opioid-exposed neonates, the risk of SIDS has been shown to relate to the severity of drug withdrawal, which correlates with the degree of maternal drug use in many studies [176].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Whereas early descriptive studies of cohorts without concurrent controls of infants born to mothers with regular opiate use during pregnancy reported SIDS rates of 21/10001 and 40/1000,2 more recent studies were unable to find an association between maternal opiate use and SIDS after controlling for potential confounders such as maternal smoking, prematurity or low birth weight 3 4. These studies, however, were either based on linking birth and death registers4 or used a case control design 3.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence for decreased height has been found in children with prenatal exposure [15,16]. Minimum evidence exists on a significant association between prenatal and/or breastfeeding marijuana exposure and risk for stillbirth, SIDS, development of depression, delinquent behavior, congenital heart lesions, psychosis, or future marijuana use [17][18][19][20][21][22][23][24][25]. Limited evidence also exists for preterm and low birth weight [26][27][28][29][30][31][32][33][34][35][36].…”
Section: Pregnancy and Breastfeedingmentioning
confidence: 99%